Analysis of the Influence of Per Capita Income and Regional Expenditure on the Reduction of Stunting Rates in Maluku Province (2016 – 2024 Period) - Terezia V. Pattimahu; Izaac Tonny Matitaputty; Maryam Sangadji; Muhammad Ridwal Assel (LP2M IAIN Palopo, 2025)
Stunting has received serious attention from the government due to its numerous influencing factors and implications for people's lives and socioeconomic conditions. This study aims to determine the influence of per capita income and regional spending on reducing stunting rates in Maluku Province. To this end, secondary data published by government agencies was collected. The data was then analyzed using multiple linear regression statistical tools. The results of the study show that per capita income has a negative and significant effect on reducing stunting rates in Maluku Province, while regional spending has a positive, although not significant, effect